The effects of self-talk on shooting athletes` motivation - Park, S.-H.; Lim, B.-S.; Lim, S.-T. (Journal of Sports Science & Medicine, 2020)
Self-talk is helpful in motivating shooting athletes and promoting effortful behavior. This study aimed to examine how the degree and intensity of self-talk of shooting athletes during matches affects their actual internal motivation and careers. In particular, the primary objective was to determine the effects of the level and intensity of self-talk on the effort value, fun and interest, tension and anxiety, and competence of intrinsic motivation for different levels of achievement and athletic performance. One hundred seventy participants who were shooting athletes registered with the Korea Shooting Federation (national team, n = 55; high performance team, n = 62; general team, n = 53). The self-talk questionnaire was developed to measure the Test of Performance Strategies (TOPS). The intrinsic motivation scale developed and applicable to sports situations was used to measure the motivation of the shooting athletes. Significant differences were observed using MANOVA as well as the basic statistics of intrinsic motivation by self-talk. The intrinsic motivation self-talk was correlated to effort value, fun and interest, and competence. There was a significant relationship between shooting athletes` self-talk and intrinsic motivation. This study indicated that athletes using self-talk experienced more fun and interest, and they perceived higher effort value and competence. Further, the multiple regression analysis revealed that self-talk affected the intrinsic motivational factors of effort value and fun and interest.